Sliding Mode Control of SolidWorks Designed Robotic Manipulator Co-simulated in MATLAB - Paidi Ravi; K. Rama Sudha (International Journal of Advanced Control and System Engineering, 2023)
This study proposes a Sliding mode control (SMC) algorithm for controlling three degrees of freedom (3DOF) robotic arm. This concept was inspired by seeing the increasing of potential applications of robotic arm in automation industry, mainly in the applications like pick and place. The 3DOF robotic arm is designed in SolidWorks and then it is imported to MATLAB for simulation purposes. Initially, simulations are done by using the conventional PID controller but the permeance is not up to the mark, the end effector takes more time to track the reference trajectory. So, to improve the results, the proposed Sliding mode controller is designed and to increase the smoothness in the end effector moment, the sliding surface is constructed by using proportional and derivative constants. A detailed derivation of this proposed SMC controller is provided in this study. For each x, y and z axis, three different trajectory paths are generated. The obtained trajectory tracking error by using this SMC controller is compared with the PID controller. According to obtained results, conclusion is that this proposed controller gives good and accurate output. The complete simulations are done in MATLAB.
Keywords: MATLAB; PID controller; Robotic Arm; SolidWorks; and Sliding Mode Control